2002
DOI: 10.1111/1467-9930.00130
|View full text |Cite
|
Sign up to set email alerts
|

Public Good, Private Protections: Competing Values in German Transplantation Law

Abstract: Organ transplantation has become almost routine practice in many industrialized countries. Policy, ethical, and legal debates tend to center on fairness of allocation rules or alternatives to promote greater numbers of donations. There are also certain beliefs about the use of bodily materials that are often presumed to be homogenous across Euro–American societies. In Germany, however, the idea of using the bodies of some for the good of others, and the right to proclaim some bodies dead for large–scale medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Thus, she pointed out how definitions of death are culturally constructed in modern medicine. For the German context, Hogle (, , ) examined the impact of two totalitarian regimes (National Socialism and German Democratic Republic) on recent national political, ethical and legal debates on organ donation. She identified how relying on Christian terminology or solidarity conflict with more recent secular and pluralistic understandings of citizenship and body concepts.…”
Section: Research Perspectives On Reluctance To Donate Organsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, she pointed out how definitions of death are culturally constructed in modern medicine. For the German context, Hogle (, , ) examined the impact of two totalitarian regimes (National Socialism and German Democratic Republic) on recent national political, ethical and legal debates on organ donation. She identified how relying on Christian terminology or solidarity conflict with more recent secular and pluralistic understandings of citizenship and body concepts.…”
Section: Research Perspectives On Reluctance To Donate Organsmentioning
confidence: 99%
“…She identified how relying on Christian terminology or solidarity conflict with more recent secular and pluralistic understandings of citizenship and body concepts. Overall, the studies of Western public attitudes have revealed that the willingness to agree to post‐mortem donation is associated with the adoption of a fragmented scientific and economic concept of the body (Hogle , Lock , Schweda and Schicktanz ). These approaches form the background of our aim as they analyse organ donation in relation to concepts of the body, theories of gifting and reciprocity, and religious concerns.…”
Section: Research Perspectives On Reluctance To Donate Organsmentioning
confidence: 99%
“…1. Germany, although it has recognized brain death as human death for a considerable time, has recently been experiencing renewed contentious debate on the subject (Hogle, 2002;Schone-Seifert, 1999). Sweden and Denmark recognized brain death as the end of human life nearly two decades after other European countries following extensive and at times vitriolic public debate on the subject (Brante and Hallberg, 1991;Rix, 1999;Machado, 1996).…”
Section: Notesmentioning
confidence: 99%
“…Although it is a shared condition for all members of humanity, there is immense variation in how it is organised and the meanings it is ascribed, both historically (Bynum, 1995) and across regions (Course, 2007;Green, 2008;Seremetakis, 1991;Verdery, 1999). Care for the dead raises basic questions relating to who owes what to whom, or what Hogle (2002) in relation to organ donation has termed the enactment of a 'moral community'. Historically, the main arenas in Western societies for negotiating state access to material remains have been dissection usage and forensic science; however, from the 1970s onwards, organ and tissue needs have taken over as the prime instigators for negotiations of access to dead bodies (Timmermans, 2006).…”
mentioning
confidence: 99%